Seed Accelerator Meet 2.0 - Nayak, Swati; Hossain, Mosharaf; Mohapatra, Subhasmita; Tyagi, Neeraj Kumar; Nath, Anirban; Singh, Vikas Kumar; Shukla, Sarvesh; Rout, Dillip Kumar; Nath, Anirban; Venkateshwarlu, Challa; Mall, Ashish; Tiwari, Ankita; et al. (International Rice Research Institute, 2025)
The Seed Accelerator Meet 2025, convened by the IRRI South Asia Hub, served as a dynamic platform to deepen strategic collaborations and drive innovation across rice breeding and seed systems in India. Against the backdrop of growing climate variability and shifting market preferences, the workshop brought together a diverse coalition of stakeholders committed to transforming the rice seed landscape through accelerated varietal turnover and inclusive seed delivery models. The workshop centered on IRRI’s One Rice Breeding and Seed System Strategy, co- developed with NARES, which prioritizes demand-driven, market-segment-based product development, on-farm validation, and coordinated scaling efforts. Discussions focused on bridging persistent gaps in varietal adoption and improving the accessibility of high- performing, climate-resilient, and market-preferred rice varieties for farmers across India. Participants from ICAR-ATARIs, state seed corporations, private seed enterprises, and farmer producer organizations converged to: Strategize on pathways to replace outdated rice varieties with superior alternatives; Strengthen forward linkages between breeders, seed agencies, and market actors; Share evidence and tools for varietal positioning and impact tracking; Explore collaborative models for ensuring that high-quality seeds reach diverse farming communities; and Address systemic bottlenecks hindering seed system responsiveness and efficiency. Special emphasis was placed on harnessing multi-stakeholder networks and data-driven decision-making to guide product selection, positioning, and adoption. The workshop also facilitated cross-learning among seed system accelerators, promoting synergy between public and private sector actors to ensure that farmers can access seeds that are both agronomically suitable and commercially viable. By reinforcing partnerships and aligning efforts across the value chain, the Seed Accelerator Meet 2025 set a renewed agenda for inclusive and sustainable seed system transformation. It reaffirmed the essential role of collaborative platforms in fostering innovation, equity, and resilience in rice production systems, ultimately contributing to enhanced food security, farm profitability, and rural livelihoods.